2000
DOI: 10.1128/aem.66.4.1720-1723.2000
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of the Effect of Fluoridated Milk on Oral Bacterial Biofilms

Abstract: Microcosmic dental plaques were grown in artificial saliva and supplemented with either milk or fluoridated milk. The presence of fluoride in the milk increased the pH of the biofilms and reduced the proportions of streptococci, demonstrating that in this model, fluoridation of milk produces biofilms with reduced cariogenic potential.Caries, one of the most prevalent diseases of humans, results from the production of acids in bacterial biofilms (dental plaques) on the tooth surface which causes localized destr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…These studies demonstrated that CDFF biofilms reflect properties that have been published for dental plaque [Bowden and Li, 1997;Wood et al, 2000] and that CDFF can be used for the initial screening of new antimicrobials under controlled conditions [Kinniment et al, 1996b;Pratten et al, 2000b].…”
mentioning
confidence: 63%
“…These studies demonstrated that CDFF biofilms reflect properties that have been published for dental plaque [Bowden and Li, 1997;Wood et al, 2000] and that CDFF can be used for the initial screening of new antimicrobials under controlled conditions [Kinniment et al, 1996b;Pratten et al, 2000b].…”
mentioning
confidence: 63%
“…Rinsing a saliva-induced biofilm in vitro with a large volume of fluoridated milk (5 ppm fluoride) reduced the numbers of streptococci throughout the biofilm, reaching a 100-fold reduction at the enamel-biofilm interface ( fig. 1) [Pratten et al, 2000]. Unfortunately, the analysis was not sufficiently detailed to predict whether the cariogenic potential of the biofilm would be reduced.…”
Section: Plaque Compositionmentioning
confidence: 99%
“…1. Viable counts of 30-Ìm-thick sections through a 624-hour bacterial biofilm grown in the presence of milk and fluoridated milk [Pratten et al, 2000]. CHX = Chlorhexidine; AmCl = amine chloride; AmF = amine fluoride.…”
Section: Adherence Of Bacteriamentioning
confidence: 99%
“…ment of caries lesions. A considerable amount of research has been conducted on investigating the influence of various foods on caries development [22][23][24] It has also been discussed, that milk and milk products may have a cariostatic effect 19,20,25 The cariostatic effect of milk and milk products may be due to their high content of Ca and P ions, the buffer capacity, or to the content of casein phosphopeptides 17,20,26 . However, there has been a controversial discussion about the fluoride availability in milk 27 .…”
Section: Discussionmentioning
confidence: 99%